2009
DOI: 10.1007/s10336-009-0453-8
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and habitat differences in concentrations of copper, zinc and arsenic in eggshells of the Rook Corvus frugilegus in Poland

Abstract: Levels of copper, zinc, and arsenic were analyzed in the Rook Corvus frugilegus eggshells from 43 breeding colonies located in different parts of Poland. The average [95% confidence interval (CI)] level of copper was found to be 8.13 (0.64-15.62) ppm, of zinc 13.81 (7.99-19.62) ppm, and of arsenic 32.57 (25.60-39.54) ppm. The concentration levels of these metals varied widely in the surveyed shells, with the difference between extreme values being 90-fold for copper, 57-fold for zinc, and 36-fold for arsenic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In general, As concentrations in passerine eggs range from 0.01 to 4.2 μg/g dw (Table 1). However, Orłowski et al (2010) found that As concentration in the eggshells of 30 of the 43 rook (Corvus frugilegus) populations studied exceeded 20 μg/g dw, an extremely high level. The authors relate these levels with the long-term accumulation in the soil due to the use of pesticides, and indicate that, at these extreme levels, As can be regarded as a threat to the growth and development of the rooks.…”
Section: Eggs and Eggshellmentioning
confidence: 88%
See 2 more Smart Citations
“…In general, As concentrations in passerine eggs range from 0.01 to 4.2 μg/g dw (Table 1). However, Orłowski et al (2010) found that As concentration in the eggshells of 30 of the 43 rook (Corvus frugilegus) populations studied exceeded 20 μg/g dw, an extremely high level. The authors relate these levels with the long-term accumulation in the soil due to the use of pesticides, and indicate that, at these extreme levels, As can be regarded as a threat to the growth and development of the rooks.…”
Section: Eggs and Eggshellmentioning
confidence: 88%
“…Nonetheless, different authors have found that As is incorporated to eggs in passerines (Dauwe et al, 1999(Dauwe et al, , 2005aMora, 2003;Orłowski et al, 2010). In general, As concentrations in passerine eggs range from 0.01 to 4.2 μg/g dw (Table 1).…”
Section: Eggs and Eggshellmentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, the highest respective mean Pb and Zn concentrations in several species of small passerines from Arizona did not exceed 1.8 Pb ppm d.w. and 79.8 Zn ppm d.w. in the egg contents and 1.5 Pb ppm d.w. and 79.8 Zn ppm in shells (for two species) (Mora 2003). Similarly, the post-hatch eggshells of the Rook Corvus frugilegus (a focal bird species of European farmland especially vulnerable to high doses of inorganic contaminants derived from their invertebrate diet obtained from crop fields) from 43 rookeries in rural and urban areas of Poland contained a mere 3.29 (range = 1.72-11.53) Pb ppm d.w. and 13.81 (range = 0.52-117.96) Zn ppm d.w. (Orłowski et al 2010(Orłowski et al , 2014b. The average Zn concentration in the egg contents of Tree Swallows Tachycineta bicolor from a wetland in Minnesota sampled between 1998 and 2001 ranged from 58.2 to 69.1 Zn ppm d.w. (Custer et al 2006).…”
Section: Levels Of Elements Of Major Environmental Concern: Potentialmentioning
confidence: 99%
“…Herons and egrets might be suitable bioindicators for the evaluation of inorganic pollution because they are top consumers in the ecosystem and can accumulate contaminants through bioaccumulation and biomagnification (Malik and Zeb 2009). Heron and egret species may inhabit water sheds with intensive agricultural areas, urban wastes, and industrial effluents (Boncompagni et al 2003;Orłowski et al 2010).…”
mentioning
confidence: 99%